THE DISTRESS OF BEING AMERICAN AS A REJECTION OF DIFFERENTIATION IN TONI MORRISON’S PARADISE - Andani, Viky; Rosyidi, Mohammad Ikhwan (Rainbow : Journal of Literature, Linguistics and Culture Studies, 2018)
America is a diverse nation. America has many races from all around the world and been recognized by the world as salad bowl. America also known for country of freedom. The fact that freedom and diversity who build America is interesting. Besides, American diversity has unique historical story which is between black and white. Paradise captures the journey and struggle of people fighting the distress of becoming American as a result of the diversity exist which create differentiation within the society of America. This study aims to find the way how to fight the distress as rejection of differentiation in the land of America and its relevant of American nowadays. The method of this study is a qualitative study analyzed by deconstruction method of Jacques Derrida. Then, the method of data analysis is based on the distress experienced by people described in the novel and how they deal with the distress. Morrison’s novel shows that differentiation within the society of America is various; race, gender, background, age, etc. but actually it can be changed. They can fight the differentiation that exist by put the distress in reverse. The final finding of this study shows that power, constructs and control the distress experienced by American which is also still relevant today.